KARAKTERISTIK TALI AGEL BERKITOSAN SEBAGAI BAHAN ALAT PENANGKAPAN IKAN - Didin Komarudin; Mulyono Baskoro; Diniah Diniah; Bambang Murdiyanto; Pipih Suptijah (Bogor Agricultural University, 2019)
Agel ropes have lower mechanical properties (breaking strength and elongation) than synthetic fiber ropes. Chitosan coating is expected to improve the mechanical properties of agel ropes. The aims of this study are to investigate the effect of immersion in chitosan on the physical and mechanical properties of agel ropes, and to examine the breaking strength and elongation of coated agel ropes after being soaked in both freshwater and seawater. This experimental study was conducted at the Laboratory of Fishing Gear Technology, Department of Fisheries Resources Utilization IPB University, and Laboratory of Forest Product Engineering, Department of Forest Products IPB University. The experiment involved 3 mm in diameter of two agel ropes incorporating control rope and agel rope soaked in 1% chitosan for 24 hours. The control rope was light brown, stiff, and rough, while the treated rope was darker, less stiff, and smoother. The breaking strength of control and treated rope was significantly different (P<0.05), which in respect constitute 15.06 kgf and 24.54 kgf. The elongation of both ropes were also significantly different (P<0.05), making 10,56% for control and 18,04% for treated rope. Breaking strength of the agel rope decreased by 50% after being immersed for 28 days. Keywords: agel rope, chitosan, breaking strength, elongation